Suitable varieties and cropping systems in underutilized crops for north west hills - Dua, R P; Phogat, B S; Raiger, H L (Indian Farming, 2015)
In hills, the underutilized crops play a significant role in agriculture for food, nutrition and house hold security for the people inhabiting in remote and inaccessible areas. These crops are nutritionally superior to the regular cereals and some of them have medicinal value also. These crops are resilient in nature and can withstand weather adversaries. The farmers have been cultivating these crops to sustain their livelihood and nutritional security. To raise the status of these poor farmers, it is important to develop superior varieties and standardize the cultivation practices and cropping systems in these crops for higher production and productivity. Several varieties have been released in crops like amaranth, buckwheat and rice bean. An analysis of the data gathered over four years revealed that the varieties ‘Annapurna’ and ‘Durga’ in amaranth; ‘Himpriya’ and ‘Himgiri’ (F. tataricum) and ‘PRB 1’ (F. esculentum) in buckwheat and ‘PRR1’ in rice bean are the best varieties in hills. Best economic yields can be obtained when amaranth and french bean are intercropped in row ratio of 1: 2 with fertilizer doze of pulses (20 N: 40 P kg/ha). In higher hills (1800-2000 m amsl) rice bean followed by pea as a vegetable crop is the most profitable crop rotation. In buckwheat early maturing varieties ‘Himgiri’ in tataricum type and ‘VL 7’ in esculentum type are best suited for double cropping system after taking either pea or potato.